Improved government capacity for County Spatial Planning in pastoral areas of Kenya derived from synthesis of research on pastoralist land use - CGIAR Research Program on Livestock (2019)
The International Livestock Research Institute (ILRI) worked with the Kenya National Land Commission (NLC) to develop an Annex to the NLC Guidelines for County Spatial Planning and three accompanying toolkits for use by staff of county governments, which were launched in 2019. This work drew on ILRI research on the use and governance of land and other resources in pastoralist settings. This research identifies a series of challenges for the management and protection of rangelands and extensive livestock production.